Los diablos de semana santa de Alangasí - Espín Guanín, Karla Franchesca (2020)
The Holy Week Devils of Alangasí are in charge of embodying the evil one in the Greater Week ceremony in the parish. This group stars in one of the most attractive and interesting days in the region, since they are frightening, bohemian, mischievous and mischievous characters in a day where respect from the parishioners, silence and reflection prevail. Ecuador is a mostly Catholic country, according to data from the Pew Research Center from 2014, 79 percent of Ecuadorian adults are Catholic, this means that Easter has a great impact, not only in Alangasí, but in everything the country. The group of devils from Alangasí has ​​been taken into account for some events in addition to Holy Week, for example it has been part of the Ethnographic Encounter of Devils in Quito which has achieved great repercussion and public interest with an attendance of 150 thousand people in its first edition. Despite the protagonism that Devils occupy in the parish, there is no deep inquiry about the group. What this journalistic investigation intends is to know the social, religious and economic dynamics that surround the Alangasí parish in Holy Week, with the group of devils of the parish as the main protagonist. As part of the state of the art of this investigation, academic and journalistic information has been collected that covers everything that has to do with the influence of Catholicism in society, the figure of evil, and Holy Week. With respect to the theoretical framework, concepts such as: religious hybridization, the devil in Catholicism, identity and religion, religious tourism, among others will be discussed. The research contains its respective methodological design that includes a qualitative approach since the techniques used are mostly interviews and participatory observation. The main sources are the members of the group of Devils of Alangasí, organizers of events that involve them, members of the GAD of Alangasí, the parish priest and all those related to the subject of the investigation.